2023
DOI: 10.1093/eurheartj/ehad100
|View full text |Cite
|
Sign up to set email alerts
|

Acyl ghrelin improves cardiac function in heart failure and increases fractional shortening in cardiomyocytes without calcium mobilization

Abstract: Background and Aims Ghrelin is an endogenous appetite-stimulating peptide hormone with potential cardiovascular benefits. Effects of acylated (activated) ghrelin were assessed in patients with heart failure and reduced ejection fraction (HFrEF) and in ex vivo mouse cardiomyocytes. Methods and results In a randomized placebo-controlled double-blind trial, 31 patients with chronic HFrEF were randomized to synthetic human acyl g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 85 publications
2
16
0
Order By: Relevance
“…In the present randomized trial, we previously reported that in patients with HFrEF, intravenous acyl ghrelin significantly increased cardiac output 4 . Here we report that acyl ghrelin caused an appropriate increase in circulating GH.…”
Section: Figuresupporting
confidence: 53%
See 2 more Smart Citations
“…In the present randomized trial, we previously reported that in patients with HFrEF, intravenous acyl ghrelin significantly increased cardiac output 4 . Here we report that acyl ghrelin caused an appropriate increase in circulating GH.…”
Section: Figuresupporting
confidence: 53%
“…Associations between selected baseline characteristics and GH response in acyl ghrelin-treated patients are depicted in online supplementary In the present randomized trial, we previously reported that in patients with HFrEF, intravenous acyl ghrelin significantly increased cardiac output. 4 Here we report that acyl ghrelin caused an appropriate increase in circulating GH. This is consistent with a previous study in HFrEF, where intravenous ghrelin increased GH and cardiac index.…”
Section: Acyl Ghrelin Infusion Increases Circulating Growth Hormone I...mentioning
confidence: 69%
See 1 more Smart Citation
“…Patients were ambulatory, had chronic HFrEF in New York Heart Association (NYHA) class III or ambulatory class IV, and a left ventricular ejection fraction (LVEF) ≤ 40%, as well as optimal guideline‐directed medical therapy at time of enrolment. Detailed inclusion and exclusion criteria were presented previously 5 . Echocardiography exams at baseline and 120 min were assessed for RV parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Ghrelin is an endogenous appetite-stimulating peptide hormone with cardiovascular actions, 1,2,3,4 which increases cardiac output (CO) in heart failure with reduced ejection fraction (HFrEF). 5 Apart from inotropic effects, animal data suggest that exogenous ghrelin administration has beneficial effects in the pulmonary vasculature. 6,7 Pulmonary hypertension (PH) and right ventricular (RV) failure are common among patients with HFrEF.…”
Section: Introductionmentioning
confidence: 99%